Analysis of agroturistic sector after first national rurl development programme (2007-2013) - Eduard Alexandru Dumitru; Laurenţiu Ionuţ Petre (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 7th Edition of the International Symposium, November 2016, Bucharest, 2016)
We can say that one of the main problems of the Romanian rural area is the high levels of poverty recorded among people in rural areas, where the main activity is agriculture of subsistence and semi-subsistence. Another problem is the state of infrastructure in the area, lack of utilities (water/sewer), is a problem that affects their quality of life and where the main problem raised by local authorities is the lack of funds.A solution that can help mitigate these problems of Romanian rural area can be the diversification of agricultural activities into non-agricultural activities. Considering the growing demand of the population for leisure in remote areas that are protected from pollution sources, and the increasing number of the Romanian population who prefer to migrate to rural areas, abandoned "parental" houses and willing to return periodically in such an environment, agro hostels would be an important factor for the economic recovery of rural space, generating new jobs, sources of revenue for municipalities in the area, but also to stop the phenomenon of migration young especially in the rural area to urban centers.However foreign tourists, with a promotion indirect (Prince Charles) are tempted by these areas in Romania, where accommodation prices are much lower compared to other regions in Europe with a tradition in the sphere of agro recognized for years but also landscapes and areas which were not affected by the development era in which we live.
Keywords: 330; agrotourism rural tourism units; rural area